Emerging information resources management and technologies - Khosrowpour, Mehdi, 1951- (Hershey : Idea Group Publishing, 2007)
"This book supplies the industry leaders, practicing managers, researchers, experts, and educators with the most current findings on undertaking the operation of the latest information technology reforms, developments, and changes. It presents the issues facing modern organizations and provides the most recent strategies in overcoming the obstacles of the ever-evolving information management and utilization industry"--Provided by publisher.
The relevance of learning processes for IT implementation / Tanya Bondarouk, Klaas Sikkel -- Salary differences between male and female software developers / Ronald Dattero, Stuart D. Galup, Jing "Jim" Quan -- Exploring the effectiveness of information security policies / Neil F. Doherty, Heather Fulford -- Competing in the marketplace : incorporating online education into higher education : an organizational perspective / Deirdre A. Folkers -- Determinant of information quality and use of executive information systems (EIS) in UK / Omar E.M. Khalil, Manal M. Elkordy -- Evidence of compensatory adaptation to unnatural media in a field study of process redesign dyads / Ned Kock -- Information technology as a target, shield, and weapon in the post 9/11 environment / Laura Lally -- An extended trust building model : comparing experiential and non-experiential factors / D. Harrison McKnight, Norman L. Chervany -- A question of timing : information acquisition and group decision making performance / Souren Paul, Carol Stoak Saunders, William David Haseman -- Progress in Internet privacy policies : a review and survey of U.S. companies from 1998 to 2006 / Alan R. Peslak -- The relationship of stategic intent to the enablers and inhibitors of e-business adoption in SMEs / Margi Levy, Philip Powell, Les Worrall -- Understanding Web site usability : the influence of Web site design parameters / Monideepa Tarafdar, Jie (Jennifer) Zhang -- Breaking out of lock-in : insights from case studies into ways to up the value ladder for Indian software SMEs / Abhishek Nirjar, Andrew Tylecote -- Comparing expert systems and agent technology for KM / Tor Guimaraes.
Includes bibliographical references and index.
Keywords: Information technology -- Management; Management information systems; Information resources management